VALIDATION OF THE CLINICIAN ATTITUDES TOWARD BIOSTATISTICS AMONG BRAZILIAN DENTISTRY GRADUATE STUDENTS - BONAFÉ, Fernanda Salloume Sampaio; COSTA, Mariana Andrade; CAMPOS, Juliana Alvares Duarte Bonini (Brazilian Journal of Biometrics, 2018)
The aim of this study was to validity of the Portuguese version of the Clinician Attitudes Toward Biostatistics (CATB) among dentistry postgraduate students. The CATB is a psychometric instrument four-factor. We evaluated the validity (λ, X2/df, CFI, TLI e RMSEA) and reliability (Cronbach's alpha (α) and Composite Reliability (CR)) of the instrument to the sample. It took part of the study 115 postgraduate students (62 master’s students, 80 women, average age 26 ± 4 years). The four-factor model did not fit the sample (λ=0.00-0.85, X2/df=1.83, CFI=0.85 e TLI=0.82 e RMSEA=0.09). After the fit of the refined orthogonal two-factor model (“Perceptions of Knowledge/Training” and “Perceptions of Biostatistics in Research and Scientific Evidence”) was found to be adequate (λ>0.45, X2/df≤2.00; CFI e TLI>0.90, RMSEA≤0.10, α e CR>0.70). The “Perception of Knowledge/Training of Biostatistics” factor was not found to be correlated with the “Perception of Biostatistics in Research and Scientific Evidence”.